Estimating Stock Returns Using Rough Set Theory: An Exploratory study With An Evidence From Iraq Stock Exchange - Adnan, Mohammed H.; Isma’eel, Mustafa Muneer (Journal of Economics and Administrative Sciences, 2021)
‎ This research aims to estimate stock returns, according to the ‎Rough Set Theory ‎approach, ‎test ‎its effectiveness and accuracy in predicting stock returns and their potential in the ‎field of ‎financial ‎markets, and rationalize investor decisions. The research sample is totaling (10) ‎companies traded at Iraq Stock Exchange. The results showed a remarkable ‎ ‎Rough Set Theory application in data reduction, contributing to the rationalization of ‎investment ‎decisions. The most prominent conclusions are the capability of rough set theory ‎in ‎dealing with financial data and applying it for forecasting stock ‎returns.‎The ‎research provides those interested in investing stocks in financial markets ‎with ‎significant financial analysis tools that exceed the traditional statistical methods. ‎The ‎originality ‎of the research lies in the diversification of financial and statistical analysis tools ‎and ‎methods of ‎forecasting stock returns